Melatonin regulates mesenchymal stem cell differentiation: a review. Issue 4 (15th April 2014) - Luchetti, Francesca; Canonico, Barbara; Bartolini, Desirée; Arcangeletti, Marcella; Ciffolilli, Silvia; Murdolo, Giuseppe; Piroddi, Marta; Papa, Stefano; Reiter, Russel J.; Galli, Francesco
Abstract Among the numerous functions of melatonin, the control of survival and differentiation of mesenchymal stem cells (MSCs) has been recently proposed. MSCs are a heterogeneous population of multipotent elements resident in tissues such as bone marrow, muscle, and adipose tissue, which are primarily involved in developmental and regeneration processes, gaining thus increasing interest for tissue repair and restoration therapeutic protocols. Receptor‐dependent and receptor‐independent responses to melatonin are suggested to occur in these cells. These involve antioxidant or redox‐dependent functions of this indolamine as well as secondary effects resulting from autocrine and paracrine responses. Inflammatory cytokines and adipokines, proangiogenic/mitogenic stimuli, and other mediators that influence the differentiation processes may affect the survival and functional integrity of these mesenchymal precursor cells. In this scenario, melatonin seems to regulate signaling pathways that drive commitment and differentiation of MSC into osteogenic, chondrogenic, adipogenic, or myogenic lineages. Common pathways suggested to be involved as master regulators of these processes are the Wnt/β‐catenin pathway, the MAPKs and the, TGF‐β signaling. In this respect melatonin emerges a novel and potential modulator of MSC lineage commitment and adipogenic differentiation. These and other aspects of the physiological and pharmacological effects of melatonin as regulator of MSC are discussed in this review.